Performance improvement of drysteam geothermal power plant by employing bottoming binary system - Dany Setyawan, Nova; Agung Pambudi, Nugroho; Utomo, Frandhoni; Huat Saw, Lip; Gürtürk, Mert; Mohammadzadeh Bina, Saeid (Institute of Physics Publishing, 2019)
This study examines on how to improve the performance of dry-steam geothermal power plants in Kamojang by utilizing the binary system. The main data taken in this research is the temperature, pressure and mass flow collected from the plant's operational data. It is then analyzed using the thermodynamic method and Engineering Equation Solver (EES). Results from the analysis showed that the net power output is about 48,865 kW. The first law efficiency increases from 16.45% to 19.44%, while the second law efficiency increases from 18.69% to 28.75%. © Published under licence by IOP Publishing Ltd.
2nd International Geothermal Conference, GEOHEAT 2018 -- 4 September 2018 through 7 September 2018 -- Petropavlovsk-Kamchatsky -- 147382
Keywords: bottoming binary system; exergy; geothermal power plant; thermodynamics